2015
DOI: 10.1007/s00737-015-0558-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between paranoid thinking, self-esteem and the menstrual cycle

Abstract: This study aimed to investigate whether paranoid experiences and levels of self-esteem fluctuate over the menstrual cycle and whether levels of self-esteem are lower when perceived persecution is felt to be deserved.Measures of anxiety, depression, persecution, deservedness and self-esteem were completed on-line by 278 women over their menstrual cycle. Responses were compared at the paramenstrual (three days before and after menses onset) and mid-cycle phase.At the paramenstrual phase persecution, negative sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…For example, many women experience physical discomfort (e.g., dysmenorrhea, breast tenderness, joint pain 5 ) around menstruation. This physical discomfort can be associated with increases in psychological distress and irritability, and decreased self-esteem 6 . Many women additionally report increased interpersonal conflicts and reduced social engagement premenstrually and during menstruation 7,8 —which may contribute to depression and isolation 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many women experience physical discomfort (e.g., dysmenorrhea, breast tenderness, joint pain 5 ) around menstruation. This physical discomfort can be associated with increases in psychological distress and irritability, and decreased self-esteem 6 . Many women additionally report increased interpersonal conflicts and reduced social engagement premenstrually and during menstruation 7,8 —which may contribute to depression and isolation 8 .…”
mentioning
confidence: 99%
“…This physical discomfort can be associated with increases in psychological distress and irritability, and decreased self-esteem. 6 Many women additionally report increased interpersonal conflicts and reduced social engagement premenstrually and during menstruation 7 , 8 —which may contribute to depression and isolation. 8 Negative affect is linked with increased impulsivity, 9 substance use, 10 and nonsuicidal self-injury.…”
mentioning
confidence: 99%
“…A meta-analysis of menstrual cycle effects on mental health outcomes, due to hormonal fluctuations, found that there is a greater risk of suicide deaths/attempts and greater risk of psychiatric admissions during menstruation [81]. Researchers have also found that self-esteem was lowest and paranoid thinking highest in the para-menstrual period (3 days before and after menstrual flow) as compared to mid-cycle [82]. However, those findings are based on data collected in the developed world and may not be as relevant to our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Constructive dealing with emotions, such as anxiety and anger (i.e. that are considered to have negative character) makes a very important aspect of the quality of one's life (Branden, 1995;Brock et al, 2016;Tsos et al, 2017;Ortenburger et al, 2015). The process of growing up is, to a large extent, learning to cope with difficult emotions (Aronson at al., 2012;Brodani & Zuskova, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms caused by anxiety and worry often are just as real as those caused by illness. The physical symptoms can become a major problem (Brock, 2016;Aronson, 2012).…”
Section: Introductionmentioning
confidence: 99%